Ceramic cutting tools : materials, development, and performance - Whitney, E. Dow (Materials science and process technology series. Ceramic and other materials--processing and technology., 1994)
Interest in ceramics as a high speed cutting tool material is based primarily on favorable material properties. As a class of materials, ceramics possess high melting points, excellent hardness, and good wear resistance. Unlike most metals, hardness levels in ceramics generally remain high at elevated temperatures, which means that cutting tip integrity is relatively unaffected at high cutting speeds. Ceramics are also chemically inert against most workmetals.